The reality of the race performance for Japanese top kayakers, and the aims of the race strategy for the 2008 Beijing Olympic - Ikeda, T.; Shibuya, K.; Oiwa, N.; Matsuo, A. (Japanese Journal of Elite Sports Support, 2009)
The purpose of this study was to investigate the reality of the race performance for Japanese top kayakers. The boat speed, stroke rate (SR), and distance per stroke (DPS) during a race were evaluated, and the variation and correlation of these parameters were examined. As a result, the following parameters were indicated as the key points for better performance in a race. 1) In 500m race, the boat speed of an initial point should be increased and a decrease in the SR after passing the initial point should be minimum. 2) In 1000m race, the boat speed in an initial point should be controlled, and a decrease of DPS should be minimum through the race. Furthermore, as a result of the race performance predicted in the 2008 Beijing Olympic, the race time of the gold medalist (500m men: 1min 36.6s, 500m women: 1min 43.5s, 1000m men: 3min 22.9s) and the concrete aims of the race strategy made it clear.